Encouraging Environmentally Sustainable Growth in Austria - Høj, Jens (OECD Publishing, 2002)
This document analyses the economic impacts of selected environmental policies in Austria with an emphasis on the use of economic instruments and incentives versus command-and-control measures. An important theme in a federation like the Austrian is the institutional complexity involved in many aspects of environmental policy, requiring a high degree of co-ordination between various layers of government, which could be furthered by a coherent ex ante and ex post evaluation system. Such a system could also be useful in the setting of abatement objectives and minimizing their associated cost. Greater use of properly designed instruments, examples being a unified taxation of fuels and the introduction of a CO2 tax, would improve the cost-effectiveness of policies to reach Austria's ambitious CO2 emission reduction target. This would particularly be the case if economic instruments replace the widespread use of subsidies and command-and-control type measures. Such measures are found to ...
Keywords: Economics; Austria